Kinerja Perusahaan Daerah Air Minum (PDAM) Tirta Amertha Jati di Kabupaten Jembrana : Performance of the Regional Drinking Water Company (PDAM) Tirta Amertha Jati in Jembrana Regency - Kayana, I Made Galih Kayana Suwikantara; Dharmanu, I Putu; Lukman, Juwita Pratiwi (Lenggogeni Data Publishing, 2024)
Organizations, both public and private organizations, compete in providing a better form of service based on the field they are working on. Discussing examples of public sector organizations, one of which is a regionally owned business entity (BUMD). One of the Regional-Owned Enterprises (BUMD) that emphasizes community service while carrying out business activities is the Regional Drinking Water Company (PDAM). PDAMs aim to provide clean water to the community, especially at the regional level, as well as assist local governments in increasing Regional Original Revenue (PAD). As part of a Regional-Owned Enterprise (BUMD), PDAM has the authority to seek profit from the service process provided to consumers. This research uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The theory used in this research is the performance theory by Dwiyanto which assesses the performance of an organization using 5 (five) indicators, namely productivity, service quality, responsiveness, responsibility, and accountability. By using this theory, it can be concluded that the performance of the Regional Drinking Water Company (PDAM) Tirtha Amertha Jati Jembrana Regency can be said to be quite good, because it still needs to be improved in several ways, such as the effective use of human resources and natural resources, infrastructure, service quality and continuity, and disaster mitigation to anticipate damage caused by natural disasters.